Service Life Prediction of Polymeric Materials - Martin, Jonathan W. (Springer, 2017)
The global marketplaceis a demanding master. To remain competitive, manufacturers must continually innovate and market advanced materials that satisfy their customers' need and expectations. Advanced in material performance and durability, however, have been hampered by our inability to measure and predict their long-term performence.